Improving subgrade support values with longitudinal drains - Marks, Vernon J.; Iowa. Highway Division. Office of Materials (Ames, Iowa : Office of Materials, Highway Division, Iowa Department of Transportation, 1984)
The trend towards rehabilitation of present roadways "generates a need for determination of roadway support ratings for rigid and composite sections. Research was initiated to determine if the Road Rater could be used to obtain structural data from these sections."
Depository.
"Interim report for Materials Laboratory Research project MLR-84-3."
Mode of access: Internet.
Keywords: Roads -- Iowa -- Subgrades -- Testing